Visual Outcomes and Pattern of Injuries among Patients presented with Ocular Trauma: a Multicenter Analysis across Urban and Peri-Urban Karachi: Doi: 10.36351/pjo.v42i1.2167 - Qidwai, Nazia; Hayat, Nausheen; Alkhairy, Saba; Mahmood, Tauseef (Pakistan Journal of Ophthalmology, 2025)
Purpose: To determine visual outcomes and pattern of injuries among patients presented with Ocular Trauma in three major tertiary care centers of Karachi. Study Design: Cross sectional study. Place and Duration of Study: Mross-sectional study conducted at three tertiary care centers of Karachi, over a 3-month period. Methods: Patients with history and signs of recent ocular and adnexal trauma were included in the study and those with any other ocular or systemic disease were excluded from the study. Data was collected on a self-designed proforma for history and the relevant ocular and adnexal examination details. Majority of the patients presented to the Accident and Emergency department and referred to Eye clinics. Ocular Trauma Scores (OTS) were calculated with the help of OTS chart. Results: In a sample of 343 patients, 44% were presented at Jinnah Postgraduate Medical Centre (JPMC), 45% at Isra Postgraduate Institute of Ophthalmology (IPIO), and 11% at Dow International Medical College (DIMC). Most injuries occurred in males (76.7%). Accidental injuries were the commonest injuries found in DIMC, (52.63%) and IPIO, (64.52%)(n=100). Whereas in JPMC, assault was the most common (31.75%). Commonest sign of ocular trauma was lid swelling (26.23%) found in DIMC and lid tear (16.76%) in JPMC. Conclusion: Ocular trauma patterns in Karachi are closely linked to the nature of surrounding environments, including traffic density, occupational hazards, and access to emergency services. Public education, protective gear enforcement, and workplace safety policies are needed to reduce the burden of preventable vision loss.